Recommendations for safer radiotherapy: what’s the message? - Dunscombe, Peter (Frontiers in Oncology, 2012)
Radiotherapy, with close to a million courses delivered per year in North America, is a very safe and effective intervention for a devastating disease. However, although rare, several deeply regrettable incidents have occurred in radiotherapy and have rightly been the subject of considerable public interest. Partly in response to reports of these incidents a variety of authoritative organizations across the globe has harnessed the expertise amongst their members in attempts to identify the measures that will make radiotherapy safer. While the intentions of all these organizations are clearly good it is challenging for the health care providers in the clinic to know where to start with so much advice coming from so many directions. Through a mapping exercise we have identified commonalities between recommendations made in seven authoritative documents and identified those issues most frequently cited. The documents reviewed contain a total of 117 recommendations. Using the 37 recommendations in “Towards Safer Radiotherapy” as the initial base layer, recommendations in the other documents were mapped, adding to the base layer to accommodate all the recommendations from the additional six documents as necessary. This mapping exercise resulted in the distillation of the original 117 recommendations down to 61 unique recommendations. Twelve topics were identified in three or more of the documents as being pertinent to the improvement of patient safety in radiotherapy. They are, in order of most to least cited: training, staffing, documentation, incident learning, communication, check lists, quality control and preventive maintenance, dosimetric audit, accreditation, minimizing interruptions, prospective risk assessment and safety culture. This analysis provides guidance for the selection of those activities most likely to enhance safety and quality in radiotherapy based on the frequency of citation in selected recent authoritative literature.